PENGARUH KESADARAN WP DAN SANKSI PERPAJAKAN PADA KEPATUHAN WP DALAM MEMBAYAR PBB - permatasari, aprillia; S., P. Dyan Yaniartha (E-Jurnal Akuntansi; Vol 1 No 2 (2012), 2012)
PBB is one of the potential sources of state revenues to continue to be explored and improved. The size of the tax revenue is determined from tax compliance in implementing the obligations in the field of taxation. This study aimed to determine the effect of Taxpayer Awareness and Tax Penalty on Tax Compliance PBB in KPP Denpasar Timur. The population in this study are all taxpayers PBB effective in KPP Denpasar Timur. The sampling method used is incidental sampling . The number of samples used in this research is 100 respondents. The data analysis technique used is multiple linear regression analysis using SPSS. Based on the analysis it is known that awareness of the taxpayer and the tax penalties positive effect on tax compliance PBB in KPP Denpasar Timur.   Keywords : compliance, tax awareness, tax penalty